Implementasi Steganografi Multi-File Menggunakan Metode Metadata PNG untuk Keamanan Data Multimedia - Muhammad Ridha; Renald Alfarizy; Muhammad Arif Mabrur; Salman Alfarisi (JIKUM: Jurnal Ilmu Komputer, 2026)
The rapid growth of digital multimedia increases the risk of unauthorized access and data leakage, requiring effective techniques to enhance data security. Steganography is one approach that conceals information within digital media to prevent detection. This research aims to implement a multi-file steganography system using the PNG metadata method to secure multimedia data. The proposed approach embeds multiple files into the metadata section of PNG images without altering the visual quality of the carrier image, thereby maintaining imperceptibility. The methodology involves analyzing PNG metadata structures, designing an embedding and extraction mechanism for multiple files, and implementing the system using a software-based approach. Experimental results demonstrate that the proposed method is capable of securely embedding and extracting multiple files while preserving image integrity and file authenticity. The use of PNG metadata provides sufficient capacity and flexibility for multi-file steganography, making it suitable for secure multimedia data storage and transmission. Overall, the proposed implementation shows that metadata-based steganography can be an effective and efficient solution for enhancing multimedia data security.